Epidemiology of candiduria and Candida urinary tract infections in inpatients and outpatients: results from a 10-year retrospective survey - Gajdács, Márió (Cent European J Urol, 2019)
INTRODUCTION: The presence of Candida species in urine (candiduria) is a common clinical finding, which may frequently represent colonization or contamination of specimens, however, they may be etiological agents in urinary tract infections (UTIs) or be indicators of underlying pathology in the genitourinary system or disseminated candidaemia. C. albicans is the most frequently isolated species of the genus, however, an increase in the occurrence of non-albicans Candida species (NACS) has been reported, which may be attributable to frequent exposure to fluconazole. MATERIAL AND METHODS: The aim of this study was to retrospectively assess and compare the prevalence of candiduria and UTIs caused by Candida spp. among inpatients and outpatients at a major clinical center in Hungary, during a 10-year period (2008–2017). RESULTS: Candiduria was detected in 0.11–0.75% of positive samples from outpatients, while this number was significantly higher for inpatients, ranging between 3.49–10.63% (p <0.001). Overall, C. albicans was the most frequently isolated species (65.22% in outpatients and 59.64% in inpatients), however, the presence of C. glabrata as a relevant etiologic agent (~20–30%) is also noteworthy, because there are corresponding therapeutic consequences. CONCLUSIONS: A pronounced female dominance (1.7–2.15-fold), advanced age (~70 years) and hospitalization of affected patients during candiduria is in line with the findings in literature.